Effect of Ezetimibe on Major Atherosclerotic Disease Events and All-Cause Mortality - Hayek, Sami (2012)
Despite ezetimibe’s ability to reduce serum cholesterol levels, there are concerns over its vascular effects and whether it prevents or ameliorates atherosclerotic disease (AD). Our objective was to estimate the effect of ezetimibe use on major AD events and all-cause mortality and to compare these associations to those observed for hydroxy-methylglutaryl-CoA reductase inhibitor (i.e., statin) use. We identified 367 new ezetimibe users between November 1, 2002 and December 31, 2009. These individuals were ≥18 years of age and had no prior statin use. One to four statin user matches were identified for each ezetimibe user resulting in a total of 1,238 closely matched statin users. Pharmacy data and drug dosage information were used to estimate a moving window of ezetimibe and statin exposure for each day of study follow-up. The primary outcome was a composite of major AD events (coronary heart disease, cerebrovascular disease, and peripheral vascular disease events) and all-cause death. Both ezetimibe use (odds ratio [OR] 0.33, 95% CI 0.13–0.86) and statin use (OR 0.61, 95% CI 0.36–1.04) were associated with reductions in the likelihood of the composite outcome. These protective associations were most significant for cerebrovascular disease events and all-cause death. Subgroup analyses by sex, race-ethnicity, prior history of AD, diabetes status, and estimated renal function showed consistent estimates across strata with no significant differences between ezetimibe and statin use. In conclusion, ezetimibe appeared to have a protective effect on major AD events and all-cause death which was not significantly different from that observed for statin use.